A first analytical report on nutritional profiling of wild and cultured Asian sea bass (Lates calcarifer) - Kanij Rukshana Sumi; Tania Akhter; Moriom Akter; Sakeb Ahmed Partho; Md. Rakibul Hasan (Applied Food Research)
Asian sea bass (Lates calcarifer) is a potential food fish found in Bangladesh's estuarine and coastal regions, but its complete nutritional profile is still unrevealed. This study exposed the first detailed nutritional profiling of wild and cultured L. calcarifer in Bangladesh. The culture was practiced using different types of live fish, such as fry of tilapia, mrigal, silver carp, shrimp, punti, etc., because of the unavailability of artificial diets for sea bass culture in Bangladesh. Protein and amino acid composition did not vary significantly (p > 0.05) between wild and cultured Asian sea bass. Lipid and fatty acid composition differed significantly (p < 0.05) between wild and cultured Asian sea bass. Substantially higher content of lipids was in cultured Asian sea bass than in the wild. Saturated fatty acid (SFA) and monounsaturated fatty acid (MUFA) did not differ between wild and cultured Asian sea bass. Polyunsaturated fatty acid (PUFA) was significantly higher in wild Asian sea bass than in cultured. The n-6/n-3 and PUFA/SFA were higher in wild Asian sea bass than in cultured. However, higher values of n-3/n-6, EPA + DHA, and FLQ were in cultured Asian sea bass than in wild. There were no significant differences between wild and cultured Asian sea bass in the case of Atherogenic Index (AI), Thrombogenic Index (TI), Hypocholesterolemic/hypercholesterolemic ratio (H/H), and Health Promoting Index (HPI) values. Considering the outcomes, it suggests using live fish instead of artificial diets in extensive farming systems could improve the nutritional value of cultured Asian sea bass.